A kind of phosphogypsum-based recycled aggregate and its preparation method and application

By preparing phosphogypsum-based recycled aggregates, the combination and static pressure forming method are used to solve the problems of low strength and long maintenance cycle of phosphogypsum recycled aggregates, and efficient utilization of phosphogypsum and improving the performance of road construction materials.

CN116283001BActive Publication Date: 2025-03-14WUHAN POLYTECHNIC UNIVERSITY +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310129486.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-16
Publication Date
2025-03-14
Estimated Expiration
2043-02-16

AI Technical Summary

Technical Problem

The existing phosphogypsum recycled aggregates have long maintenance cycle, low strength, porous surface, and strong water absorption, which leads to poor mechanical properties and long-term road performance, and cannot replace natural sand and gravel aggregates in large proportion for road construction.

Method used

By preparing a phosphogypsum-based recycled aggregate, the compounding scheme of calcined phosphogypsum, slag, silicate cement, sodium hydroxide and water is used, and combined with static pressure forming method and natural curing technology, the utilization rate of phosphogypsum and the strength and density of the aggregate are improved.

Benefits of technology

It has achieved high utilization, high strength and short maintenance cycle of phosphogypsum-based recycled aggregates, and can replace natural sand and gravel aggregates in large proportion for road construction, significantly improving economic, environmental and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116283001B_ABST
    Figure CN116283001B_ABST
Patent Text Reader

Abstract

The present invention discloses a phosphogypsum-based recycled aggregate and a preparation method and application thereof, and belongs to the technical field of road construction materials. The phosphogypsum-based recycled aggregate, per 100 parts by weight of raw materials, includes the following components: 49.64-60.28 parts of calcined phosphogypsum, 7.09-14.23 parts of slag, 3.55-10.67 parts of Portland cement, 0.36-0.71 parts of sodium hydroxide, and 28.37-28.47 parts of water. The present invention effectively utilizes the synergistic effect between the components through the compounding of multiple materials, has a small number of raw material types, a large proportion of phosphogypsum, and a simple and efficient molding process. The prepared phosphogypsum-based recycled aggregate only requires natural conditions for maintenance and has a short maintenance period. 、 It has high strength and can be widely used in road construction. It has significant economic, environmental and comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road engineering materials, and in particular to a phosphogypsum-based recycled aggregate and a preparation method and application thereof. Background Art

[0002] As the demand for highway construction and maintenance in my country continues to increase, the demand for the amount and quality of road aggregates continues to increase. In addition, under strict environmental protection requirements, the mining of natural sand and gravel is limited, the supply is tight, and the price is rising. Sand and gravel aggregates are the basic materials in road construction and maintenance projects, and the amount is large. If natural sand and gravel aggregates are used continuously, it will cause serious threats to the ecological resources and environment. Therefore, recycled aggregates, especially solid waste recycled aggregates, have excellent economy and environmental protection, which meet the functional and environmental protection requirements of road construction.

[0003] Phosphogypsum is the solid waste residue produced by the decomposition of phosphate ore during the wet production of phosphoric acid. The production of 1 ton of phosphoric acid produces about 5 tons of phosphogypsum, which mainly exists in the form of dihydrate gypsum or hemihydrate gypsum. my country is a major producer of phosphate fertilizers and a major emitter of phosphogypsum. In 2021, the output of my country's phosphogypsum industry was about 74.6 million tons. However, as an acidic industrial solid waste, phosphogypsum is difficult to utilize and has a low utilization rate. In 2021, the comprehensive utilization rate of phosphogypsum in my country was less than 48.0%. At present, the treatment methods of phosphogypsum are mainly divided into comprehensive utilization and stockpiling, among which stockpiling is the main method. At present, the total stockpile of phosphogypsum in my country is about 600 million tons, and the annual output is about 40 million tons. The environmental problems caused by such a huge amount of phosphogypsum accumulation have gradually become prominent, which has aroused great concern from the society and the government. Therefore, proposing application scenarios of phosphogypsum-based recycled materials with high utilization rate, good comprehensive performance and large-scale promotion is a key measure to quickly solve the problem of phosphogypsum stockpiling.

[0004] Phosphogypsum-based recycled aggregates can not only solve the environmental problems caused by the large-scale mining of natural sand and gravel aggregates, but also achieve large-scale recycling of phosphogypsum, promote the resource-based and reduced utilization of phosphogypsum, and have significant economic, environmental and social benefits. However, the current research on phosphogypsum recycled aggregates has problems such as long maintenance cycle, low strength, porous surface, and strong water absorption due to the use of traditional granulation technology or the use of only phosphogypsum as a cementitious material, resulting in poor mechanical properties and long-term road performance of granulated aggregates, and cannot replace natural sand and gravel aggregates in large proportions for road construction. Summary of the invention

[0005] In view of the above shortcomings, the object of the present invention is to provide a phosphogypsum-based recycled aggregate and a preparation method and application thereof. The phosphogypsum-based recycled aggregate prepared by the present invention has high phosphogypsum utilization rate, short maintenance period, high strength, and can be widely used in road construction.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions:

[0007] A phosphogypsum-based recycled aggregate comprises the following components per 100 parts by weight of raw materials: 49.64-60.28 parts of calcined phosphogypsum, 7.09-14.23 parts of slag, 3.55-10.67 parts of Portland cement, 0.36-0.71 parts of sodium hydroxide and 28.37-28.47 parts of water.

[0008] Furthermore, the calcined phosphogypsum is obtained by calcining the original phosphogypsum, which is a solid waste generated in the wet phosphoric acid process, at 180 to 220° C. for 18 to 22 minutes.

[0009] Furthermore, the particle size of the calcined phosphogypsum is 100-200 meshes.

[0010] Furthermore, the slag is water-quenched granulated blast furnace slag produced by ironmaking, and the grade is S95.

[0011] Furthermore, the silicate cement is ordinary silicate cement with a strength grade of 42.5.

[0012] Furthermore, the sodium hydroxide is analytically pure, and the sodium hydroxide content is not less than 96%.

[0013] The present invention also provides a method for preparing the above-mentioned phosphogypsum-based recycled aggregate, comprising the following steps:

[0014] Calcined phosphogypsum, slag and Portland cement are mixed uniformly according to weight to obtain a mixture A;

[0015] Take sodium hydroxide and add it into water, stirring to fully dissolve it to obtain mixture B;

[0016] Mixing mixture B and mixture A uniformly to obtain mixture C;

[0017] The mixture C is placed into a mold and statically pressed into shape, and after demoulding, naturally cured to obtain a solidified product D;

[0018] The solidified material D is crushed and sieved to obtain phosphogypsum-based recycled aggregate.

[0019] Furthermore, in the process of loading the mixture C into a mold and performing static pressure molding, the static pressure molding pressure is 1200 to 1800 kN, and the static pressure molding time is 1 to 3 minutes.

[0020] Furthermore, the natural curing time is 1 to 7 days.

[0021] The present invention also provides an application of the phosphogypsum-based recycled aggregate or the phosphogypsum-based recycled aggregate prepared by the above-mentioned preparation method in road construction.

[0022] The beneficial effects of the present invention are:

[0023] (1) The present invention effectively utilizes the synergistic effect between the components through the compounding of multiple materials. The activity of calcined phosphogypsum can promote the hydration reaction of siliceous and aluminous raw materials, and the hemihydrate gypsum dissolves rapidly in water, thereby improving the strength and water resistance of the phosphogypsum aggregate. By adding silicate cement and active admixtures, not only the calcined phosphogypsum and the cementitious material are promoted to undergo a chemical reaction to produce a high-strength calcium sulfonate skeleton, thereby reducing the moisture content and increasing the density and strength. In addition, alkaline materials such as silicate cement and active admixtures reduce the acidity of phosphogypsum, thereby reducing the corrosion risk faced by engineering structures and equipment during use, and realizing the stable application of a large proportion of phosphogypsum-based recycled aggregates.

[0024] (2) The present invention realizes the large-scale recycling and utilization of various industrial solid wastes, reduces the storage of industrial solid wastes, and has significant environmental benefits.

[0025] (3) Compared with the traditional granulation process, the present invention adopts static pressure molding to first mold and then crush, which has high molding efficiency. The prepared aggregate is closer to natural crushed stone, so it can replace natural sand and gravel aggregate in a large proportion for road construction.

[0026] (4) The total solid waste content of the present invention accounts for a large proportion, which minimizes the use of cement and other admixtures. In addition, the raw materials and aggregates do not need to be processed or maintained under special conditions during the preparation process. The molding process is simple and efficient, and the maintenance conditions are natural maintenance. Compared with other molding and maintenance methods, it has strong operability, high efficiency, and low cost, and has significant economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0028] Figure 1 The phosphogypsum-based recycled aggregate prepared by the present invention;

[0029] Figure 2 It is a phosphogypsum-based recycled aggregate prepared by traditional methods. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The embodiment of the present invention provides a phosphogypsum-based recycled aggregate, wherein 100 parts by weight of raw materials include the following components: 49.64 to 60.28 parts of calcined phosphogypsum, 7.09 to 14.23 parts of slag, 3.55 to 10.67 parts of Portland cement, 0.36 to 0.71 parts of sodium hydroxide, and 28.37 to 28.47 parts of water.

[0032] Among them, the calcined phosphogypsum is obtained by calcining the original phosphogypsum, which is a solid waste generated in the wet phosphoric acid process, at 180 to 220° C. for 18 to 22 minutes. The particle size of the calcined phosphogypsum is 100 to 200 meshes.

[0033] In some embodiments, the slag is water-quenched granulated blast furnace slag produced by ironmaking, and the grade is S95; the silicate cement is ordinary silicate cement with a strength grade of 42.5; the sodium hydroxide is analytically pure, and the sodium hydroxide content is not less than 96%.

[0034] In the above material system, the calcined phosphogypsum component is always present in excess. When water is added, the cement begins to undergo a rapid hydration reaction, producing a large amount of CSH gel and Ca(OH)2, which initially provides strength to the system. At the same time, the hemihydrate calcium sulfate component of the calcined phosphogypsum will also become CaSO4·2H2O when it comes into contact with water, and undergo a hydration reaction with tricalcium aluminate (C3A) in the cement. In the presence of CaSO4·2H2O and Ca(OH)2, ettringite needle-shaped crystals (AFt) are eventually generated. The ettringite crystals will be deposited on the surface of cement particles, hindering further contact between cement particles and water, thereby reducing the water content and delaying the cement setting time.

[0035] When active mineral admixture slag exists in the material system, since the active mineral admixture contains a large amount of active SiO2 and Al2O3 components, it can interact with Ca(OH)2 produced by cement hydration to generate hydrated calcium silicate and hydrated calcium aluminate. Hydrated calcium silicate can be converted into gel, while hydrated calcium aluminate further reacts with calcined phosphogypsum to generate ettringite. Therefore, with the participation of active mineral admixtures, more calcined phosphogypsum particles participating in the chemical reaction to be converted into ettringite are present in the system, and the increase in ettringite crystals will cause the fiber rod-like crystals of the material system to overlap and overlap to form a dense network structure, so the overall strength of the material system is significantly improved.

[0036] Since different types of active mineral admixtures have different components, they will play different roles under the same hydration environment. Sodium hydroxide can provide the material system with the alkalinity required for the reaction, stimulate the potential activity of the active mineral admixture, accelerate the hydration reaction process on the one hand, and increase the amount of ettringite crystals in the material system on the other hand, thus significantly increasing the strength of the material system.

[0037] The method for preparing the above-mentioned phosphogypsum-based recycled aggregate comprises the following steps:

[0038] (1) taking calcined phosphogypsum, slag and Portland cement in parts by weight and mixing them uniformly to obtain a mixture A;

[0039] (2) adding sodium hydroxide into water and stirring to fully dissolve the sodium hydroxide to obtain a mixture B;

[0040] (3) mixing mixture B and mixture A uniformly to obtain mixture C;

[0041] (4) The mixture C is placed into a mold and statically pressed at a pressure of 1200 to 1800 kN for 1 to 3 minutes, and after demolding, naturally cured for 1 to 7 days to obtain a cured product D;

[0042] (5) The solidified material D is crushed and sieved to obtain phosphogypsum-based recycled aggregate.

[0043] In summary, the present invention designs a reasonable compounding scheme based on the physical and chemical properties of phosphogypsum, mineral powder and cement, and utilizes the interaction between the three materials to increase the utilization of solid waste, effectively solving the problem of low utilization rate of phosphogypsum. In addition, the calcined phosphogypsum and active admixtures are solidified by static pressure molding, and the prepared phosphogypsum-based recycled aggregate has the characteristics of high density, high strength, and short maintenance cycle. In summary, the present invention can greatly improve the consumption and utilization efficiency of phosphogypsum, and achieve the goals of reducing phosphogypsum stockpiling, reducing production costs, and avoiding potential secondary pollution. And the phosphogypsum-based recycled aggregate produced by the present invention can be widely used in road construction, with outstanding social and economic benefits.

[0044] The present invention is further described in detail below through specific examples.

[0045] Natural curing in the present invention refers to naturally storing the aggregate after demoulding at room temperature.

[0046] The calcined phosphogypsum in the embodiment of the present invention is obtained by calcining the original phosphogypsum, which is solid waste produced in the wet phosphoric acid process, at 180-220° C. for 18-22 minutes. Before use, it is first dried and then ball-milled to a particle size of 100-200 meshes. The slag is water-quenched granulated blast furnace slag produced by ironmaking, and the grade is S95. The silicate cement is ordinary silicate cement with a strength grade of 42.5. The sodium hydroxide is analytically pure, and the sodium hydroxide content is not less than 96%. The water is ordinary tap water.

[0047] Example 1

[0048] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 53.19 parts: 7.09 parts: 10.64 parts: 0.71 parts: 28.37 parts.

[0049] Example 2

[0050] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 53.38 parts: 14.23 parts: 3.56 parts: 0.36 parts: 28.47 parts.

[0051] Example 3

[0052] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 53.19 parts: 14.18 parts: 3.55 parts: 0.71 parts: 28.37 parts.

[0053] Example 4

[0054] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 53.38 parts: 10.67 parts: 7.12 parts: 0.36 parts: 28.47 parts.

[0055] Example 5

[0056] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 49.64 parts: 14.18 parts: 7.09 parts: 0.71 parts: 28.37 parts.

[0057] Example 6

[0058] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 49.82 parts: 14.23 parts: 7.12 parts: 0.36 parts: 28.47 parts.

[0059] Example 7

[0060] Calcined phosphogypsum: slag: Portland cement: sodium hydroxide: water = 60.28 parts: 7.09 parts: 3.55 parts: 0.71 parts: 28.37 parts.

[0061] The phosphogypsum-based recycled aggregates of Examples 1 to 7 were prepared according to the following method:

[0062] First, calcined phosphogypsum, slag and silicate cement are weighed in proportion and mixed and mechanically stirred for 2 minutes; then, sodium hydroxide in the proportion of the ingredients is added to the water in the proportion of the ingredients and stirred to fully dissolve, and the mixture is added into a mixer together with the stirred calcined phosphogypsum, slag and cement mixture. After stirring for 3 minutes, the mixture is put into a mold and statically pressed for 2 minutes at a pressure of 1500 kN. The pressurization method adopts the method of increasing the force as the unit and the speed is set to 10-20 kN / s. After demolding, the solidified material is naturally cured for 1 day to obtain the solidified material, which is then crushed by a crusher and sieved to obtain aggregates of different particle sizes.

[0063] Comparative Example 1

[0064] Calcined phosphogypsum: water = 71.43 parts: 28.57 parts.

[0065] Firstly, calcined phosphogypsum and water were weighed according to the proportion of ingredients, added into a mixer and stirred for 3 minutes, and then molded. Then, static pressing was performed at a pressure of 1500 kN for 2 minutes, and then demolding was performed. After natural curing for 1 day, a solidified material was obtained, which was crushed by a crusher and sieved to obtain aggregates of different particle sizes.

[0066] Comparative Example 2

[0067] Calcined phosphogypsum: Portland cement: water = 57.14 parts: 14.29 parts: 28.57 parts.

[0068] Firstly, calcined phosphogypsum and ordinary Portland cement were weighed according to the proportion of ingredients, mixed and mechanically stirred for 2 minutes, then added into a mixer together with water, stirred for 3 minutes and then filled into a mold. After static pressing at a pressure of 1500 kN for 2 minutes, the mold was demolded and naturally cured for 1 day to obtain a solidified material, which was crushed by a crusher and sieved to obtain aggregates of different particle sizes.

[0069] Comparative Example 3

[0070] The preparation method is the same as that of Comparative Example 2, except that calcined phosphogypsum: Portland cement: water = 67.86 parts: 3.57 parts: 28.57 parts.

[0071] Comparative Example 4

[0072] Calcined phosphogypsum: slag: water = 57.14 parts: 14.29 parts: 28.57 parts.

[0073] Firstly, calcined phosphogypsum and slag were weighed according to the proportion of ingredients, mixed and mechanically stirred for 2 minutes, then added into a mixer together with water, stirred for 3 minutes and then filled into a mold. After static pressing at a pressure of 1500 kN for 2 minutes, demolding was carried out. After natural curing for 1 day, a solidified material was obtained, which was crushed by a crusher and sieved to obtain aggregates of different particle sizes.

[0074] Comparative Example 5

[0075] Calcined phosphogypsum: Portland cement: sodium hydroxide: water = 56.74 parts: 14.18 parts: 0.71 parts: 28.57 parts.

[0076] First, calcined phosphogypsum and silicate cement are weighed according to the proportion of ingredients, mixed and mechanically stirred for 2 minutes, sodium hydroxide is added into water and stirred to make it fully dissolved, and then added into a mixer and stirred for 3 minutes before filling into a mold. After static pressing at a pressure of 1500 kN for 2 minutes, demolding is performed, and a solidified material is obtained after natural curing for 1 day. After crushing with a crusher, the aggregates of different particle sizes are sieved.

[0077] Comparative Example 6

[0078] Calcined phosphogypsum: slag: sodium hydroxide: water = 56.74 parts: 14.18 parts: 0.71 parts: 28.57 parts.

[0079] Firstly, calcined phosphogypsum and slag are weighed according to the proportion of ingredients, mixed and mechanically stirred for 2 minutes, sodium hydroxide is added into water and stirred to make it fully dissolved, and then added into a mixer and stirred for 3 minutes before filling into a mold, and demolded after static pressing at a pressure of 1500 kN for 2 minutes. After natural curing for 1 day, a solidified material is obtained, which is crushed by a crusher and sieved to obtain aggregates of different particle sizes.

[0080] Comparative Example 7

[0081] Calcined phosphogypsum: slag: Portland cement: water = 53.57 parts: 14.29 parts: 3.57 parts: 28.57 parts.

[0082] Firstly, calcined phosphogypsum, slag and silicate cement were weighed according to the proportion of ingredients, mixed and mechanically stirred for 2 minutes, then added into a mixer together with water, stirred for 3 minutes and then molded. After static pressing at a pressure of 1500 kN for 2 minutes, demolding was carried out. After natural curing for 1 day, a solidified material was obtained, which was crushed by a crusher and sieved to obtain aggregates of different particle sizes.

[0083] For the convenience of comparison, the raw material dosages of the above embodiments and comparative examples are listed, as shown in the following Table 1.

[0084] Table 1 Raw material dosage of each embodiment of the present invention and comparative example (parts by weight)

[0085]

[0086]

[0087] The compressive and flexural strengths of the solidified specimens of the above embodiments and comparative examples and the crushing values ​​of the crushed aggregates were tested, wherein:

[0088] The flexural strength and compressive strength are calculated by averaging the flexural strength of three specimens of each group of solidified materials. The crushing value is used to measure the ability of aggregates to resist crushing under gradually increasing loads and is an indicator of the mechanical properties of aggregates.

[0089] The test results of the 3d and 7d compressive and flexural strengths of the cured specimens of the embodiments of the present invention and the comparative examples, and the crushing value of the crushed aggregate after curing for 1 day are shown in Table 2.

[0090] Table 2 Test results of compressive flexural strength and crushing value of various embodiments of the present invention and comparative examples

[0091]

[0092] It can be seen from Comparative Examples 1 to 4 that when the material system components are only one or two, the synergistic effect cannot be effectively exerted. And by comparing Comparative Examples 2 and 3, it can be seen that although Comparative Example 2 with a high cement dosage (cement accounts for 20%) has higher mechanical properties, when the cement dosage is reduced to 5%, the 3d and 7d compressive and flexural strengths are both reduced, and the crushing value increases. However, the mechanical properties of the embodiments of the present invention are still better than those of the control examples with high cement dosage even at low cement dosage (accounting for 5%) under the synergistic mechanism, which meets the needs of energy saving and carbon reduction.

[0093] It can be seen from Comparative Examples 5 and 6 that, under the premise of the same calcined phosphogypsum and sodium hydroxide dosage, the mechanical properties of only compounding with cement or only compounding with slag are significantly lower than those in the examples.

[0094] It can be seen from Comparative Example 7 and Examples 2 and 3 that, under the premise of the same calcined phosphogypsum, cement and slag dosage, the mechanical properties when sodium hydroxide is not used as an activator are significantly weaker than those of the examples, and different dosages of sodium hydroxide have a great influence on the 3d and 7d compressive flexural strengths and the 1d crushing value, among which Example 3 has the best mechanical properties.

[0095] The present invention uses a suitable proportion of calcined phosphogypsum, slag, silicate cement, sodium hydroxide and water for compounding, so that the crushing value and compressive strength are significantly improved, and the flexural strength is also improved to a certain extent, indicating that the solidified material obtained in the embodiment of the present invention has the characteristics of high strength and high density, and the 7d compressive strength is 23.68-30.45MPa, which is significantly better than the control example. And the crushing value (22.30-24.32%) of the crushed aggregate after natural curing for 1 day is also reduced to varying degrees, so the strength is higher when used as road aggregate.

[0096] Figures 1-2 They are respectively the phosphogypsum-based recycled aggregate prepared by the present invention and the recycled aggregate prepared by the traditional spherical granulation process. It can be seen that compared with the nearly spherical aggregate prepared by the traditional process, the present invention adopts a static pressure method to form and then crush, and the forming efficiency is higher. The prepared aggregate is similar to natural crushed stone, with better angularity, which is conducive to the interlocking effect between aggregates to form a high-strength skeleton. The aggregate prepared by the present invention can directly refer to the existing specifications to replace part or all of the natural crushed stone for grading design, so it has stronger applicability and better performance in road engineering.

[0097] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0098] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A phosphogypsum-based recycled aggregate, characterized in that: The raw materials per 100 parts by weight include the following components: 49.64-60.28 parts of calcined phosphogypsum, 7.09-14.23 parts of slag, 3.55-10.67 parts of Portland cement, 0.36-0.71 parts of sodium hydroxide, and 28.37-28.47 parts of water; the slag is water-quenched granulated blast furnace slag produced by ironmaking, and the grade is S95; The method for preparing the phosphogypsum-based recycled aggregate comprises the following steps: Calcined phosphogypsum, slag and Portland cement are mixed uniformly according to weight to obtain a mixture A; Take sodium hydroxide and add it into water, stirring to fully dissolve it to obtain mixture B; Mixing mixture B and mixture A uniformly to obtain mixture C; The mixture C is placed into a mold and statically pressed, and then naturally cured after demoulding to obtain a solidified product D; The solidified material D is crushed and sieved to obtain the phosphogypsum-based recycled aggregate.

2. The phosphogypsum-based recycled aggregate according to claim 1, characterized in that: The calcined phosphogypsum is obtained by calcining the original phosphogypsum, which is solid waste generated in the wet phosphoric acid process, at 180-220° C. for 18-22 minutes.

3. The phosphogypsum-based recycled aggregate according to claim 1, characterized in that: The particle size of the calcined phosphogypsum is 100-200 meshes.

4. The phosphogypsum-based recycled aggregate according to claim 1, characterized in that: The silicate cement is ordinary silicate cement with a strength grade of 42.

5.

5. The phosphogypsum-based recycled aggregate according to claim 1, characterized in that: The sodium hydroxide is analytically pure, and the sodium hydroxide content is not less than 96%.

6. The phosphogypsum-based recycled aggregate according to claim 1, characterized in that: In the process of loading the mixture C into the mold and performing static pressure molding, the static pressure molding pressure is 1200-1800 kN, and the static pressure molding time is 1-3 min.

7. The phosphogypsum-based recycled aggregate according to claim 1, characterized in that: The natural curing time is 1 to 7 days.

8. Use of the phosphogypsum-based recycled aggregate according to any one of claims 1 to 7 in road construction.

Citation Information

Patent Citations

  • Burning-free light aggregate, lightweight concrete, and preparation methods of burning-free light aggregate and lightweight concrete

    CN106986568A

  • Gypsum-based unfired aggregate

    CN113121138A

  • Green artificial aggregate based on phosphogypsum and preparation method thereof

    CN115677306A